Analysis of the Application of Linear Interpolation and Quadratic Interpolation in Electrical Distribution Performance - Siswandari Noertjahjani; Syafiq Abdul Zaki; Aris Kiswanto (University of Respati Yogyakarta, Indonesia, 2024)
The electricity distribution network is an important component that distributes electricity from substations to end consumers. Monitoring voltage across the network is critical, but direct measurement at all points is often impractical due to resource limitations. This research uses linear interpolation and quadratic interpolation to estimate stress at unmeasured points. Voltage measurement data at several points is used as a basis for interpolation. With the help of MATLAB, the voltage at unmeasured points can be estimated quickly and accurately. The results of the interpolation of distance on electricity consumption show that electricity consumption decreases as distance increases. At a distance of 5 km (Ds. Galih), electricity consumption was recorded at 1,237.5 kWh, while at a distance of 15 km (Ds. Triharjo) electricity consumption was reduced to 1,232.5 kWh. Furthermore, at a distance of 25 Km (Wungurejo District), electricity consumption was recorded at 1,227.5 kWh, and at a distance of 35 Km (Tejorejo District) electricity consumption decreased again to 1,222.5 kWh. This method enables more comprehensive monitoring of network performance, helps identify areas that require special attention, and supports decisions in network maintenance and repair. In conclusion, linear interpolation is an effective method for estimating voltages in electrical distribution networks, making an important contribution to improving the reliability and efficiency of electrical power distribution. Assists in monitoring and analyzing the performance of the electricity distribution network, thereby enabling more targeted maintenance and repair actions.